Dynamic analysis of layered systems under a moving harmonic rectangular load based on the spectral element method. (15th December 2019) - Sun, Zhaojie; Kasbergen, Cor; Skarpas, Athanasios; Anupam, Kumar; van Dalen, Karel N.; Erkens, Sandra M.J.G.
Highlights: A semi-analytical 3D model is developed for layered systems under a moving load. This model is a potential tool for pavement structural design. This model is a promising parameter back-calculation engine. Abstract: In order to design high-performance roadways, a robust tool which can compute the structural response caused by moving vehicles is necessary. Therefore, this paper proposes a spectral element method-based model to accurately and effectively predict the 3D dynamic response of layered systems under a moving load. A layer spectral element and a semi-infinite spectral element are developed to respectively model a layer and a half-space, and the combinations of these two elements can simulate layered systems. The detailed mathematical derivation and numerical validation of the proposed model are included. Additionally, this model is used to investigate the dynamic characteristics of a pavement structure under a moving harmonic rectangular load. The results show that the proposed model can accurately predict the dynamic response of layered systems caused by a moving load. It is also found that the vertical displacement amplitude curves of surface points caused by a moving harmonic load are asymmetric along the moving direction, and this property is more dominant at higher velocities. In addition, the amplitudes of these vertical displacements are smaller if the loading frequency is higher or the loss factor is bigger. Finally, the loading area and Poisson's ratio only have effect on the displacement amplitudes of points in the close vicinity of the loading area. The proposed model is beneficial to the development of engineering methods for pavement design and is a promising parameter back-calculation engine for pavement quality evaluation.